2017
DOI: 10.1515/jtim-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in patients with end stage renal disease: causes, characteristics and factors associated with need for endoscopic therapeutic intervention

Abstract: Background and Objectives: The risk of upper gastrointestinal bleeding (UGIB) is increased among the end-stage renal disease (ESRD) patients. The aim of the current study was to describe the causes and characteristics of UGIB in ESRD patients at our center and to assess the need for endoscopic therapeutic intervention (ETI) using Rockall (RS) and Glasgow Blatchford scores (GBS). Material and Methods: All patients with ESRD and UGIB with age ≥14 years were included. Frequencies and percentages were computed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Laeeq et al described the causes and characteristics of UGIB in ESRD patients and found that the most common findings were erosions (55.9%) and ulcers (30.3%). More than half (55.9%) of patients required therapeutic intervention [22].…”
Section: Anemia and Gi Bleeding In Ckdmentioning
confidence: 99%
“…Laeeq et al described the causes and characteristics of UGIB in ESRD patients and found that the most common findings were erosions (55.9%) and ulcers (30.3%). More than half (55.9%) of patients required therapeutic intervention [22].…”
Section: Anemia and Gi Bleeding In Ckdmentioning
confidence: 99%
“…Several studies have demonstrated high mortality with higher Rockall scores[ 6 ]. However, Laeeq et al[ 7 ] have not found significantly higher mortality in patients with high pre-endoscopic Rockall score (> 5). The Rockall score only assesses the risk of mortality in patients with upper GI bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with gastric glomus tumor can present different symptoms, such as abdominal discomfort or pain, and gastric glomus tumor is one of rare causes of gastrointestinal hemorrhage. [11][12][13][14] One patient (1/11) presented with upper gastrointestinal bleeding in our report.…”
Section: Disscussionmentioning
confidence: 56%